Theoretical study of B2 type technetium AB (A=Tc, B=Ti, V, Nb and Ta) intermetallic compounds. (December 2016) - Acharya, Nikita; Fatima, Bushra; Sanyal, Sankar P.
Abstract: The structural, electronic, elastic and thermal properties of the cubic AB type (A=Tc, B=Ti, V, Nb and Ta) technetium intermetallic compounds have been studied using the full potential linearized augmented plane wave (FP-LAPW) method within the generalized gradient approximation (GGA) and local density approximation (LDA) used for the exchange-correlation potential. The calculated lattice parameters agree well with the experimental results. The calculated electronic properties reveal that these compounds are metallic in nature with partial ionic bonding. The elastic constants obey the stability criteria for cubic system. Ductility for these compounds has been analyzed using the Pugh's rule and Cauchy's pressure revealing ductile in nature of all the compounds. Bonding nature is discussed using Fermi surface, band structure and charge density difference plots. Graphical abstract: Fermi surfaces plots in B2 phase for TcTi (a, b, c), TcV (d, e, f, g, h), TcNb (i, j, k, l) and TcTa (m, n, o, p). Highlights: The DFT calculations have been performed for AB (A=Tc, B=Ti, V, Nb and Ta). Ductility analyse using Pugh's rule, Cauchy's pressure and Poisson's ratio. Structural, elastic and thermal properties are reported in GGA and LDA approx. Contour plots show ionic-covalent and metallic character.